Public Sector and Budgetary Economy in Transition in Poland in a New Context ofDevelopment Economics - Jarosiński, Krzysztof (European Journal of Economics and Business Studies, 2017)
The subject of the paper is to present selected problems of the budgetary economy of enterprises an organizational units of the public sector. The main focus is to explore the relations between the principles of thebudgetary economy of the public sector units against assumptions of new concepts of economic development. This study refers also to the idea of development economics because the systemic transition towards the marketeconomy in Poland required reconstruction of the economy and the creation of new political, organizational and social structures. In the presented study there were applied analytical methods relating to the empirical data andalso analytical methods related to the finances of the public sector. Research methods referred to the theoretical analysis of literature and empirical analysis of the relations between phenomena occurring in the real economyand in the public sector. Preliminary studies indicated that it was not possible to conduct economic policies and maximize tax revenue, particularly by escalating tax burden. Budgetary economy should therefore be conducted according to the principles of rationality and efficiency of resource use. The increase of the budgetary revenues of these group of public sector units must lead to negative consequences, and in particular to increase of the range of the shadow economy.
Keywords: budgetary economy, local and regional development, public finances, taxation.